ФУНКЦИОНАЛЬНЫЕ ГАСТРОИНТЕСТИНАЛЬНЫЕ РАССТРОЙСТВА У ДЕТЕЙ ШКОЛЬНОГО ВОЗРАСТА, ПЕРЕНЕСШИХ COVID-19 - Налетов, Андрей Васильевич; Свистунова, Наталия Александровна; Мацынина, Наталья Ивановна; Сердюкова, Дарья Андреевна (FORCIPE, 2022)